Warfarin-induced skin necrosis: A ‘novel’ solution to an old problem - Cantürk, Emir; Karaca, Oğuz; Omaygenç, Onur; Kızılırmak, Filiz; Güler, Ekrem (My University, 2014)
We present two cases of skin necrosis occurring after initiation of warfarin therapy, bpth of wich were safely treated with novel oral anti-coagulants (NO-ACs). The first case is a 52-years-old male, seen after a transient ischemic event.
Varfarine bağlı cilt nekrozu: Eski bir soruna yeni bir çözüm
Keywords: Warfarin; Skin Necrosis; Varfarin; Cilt Nekrozu